2016
DOI: 10.1038/srep24565
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Self-Assembled Grain Like Curcumin Conjugated ZnO: Curcumin Conjugation Enhances Removal of Perylene, Fluoranthene and Chrysene by ZnO

Abstract: Curcumin conjugated ZnO, referred as Zn(cur)O, nanostructures have been successfully synthesized, these sub-micro grain-like structures are actually self-assemblies of individual needle-shaped nanoparticles. The nanostructures as synthesized possess the wurtzite hexagonal crystal structure of ZnO and exhibit very good crystalline quality. FT-Raman and TGA analysis establish that Zn(cur)O is different from curcumin anchored ZnO (ZnO@cur), which is prepared by physically adsorbing curcumin on ZnO surfaces. Chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 49 publications
1
22
2
Order By: Relevance
“…, is proposed. Curcumin has a HOMO–LUMO gap of 2.64 eV in the visible range . The HOMO of curcumin is at 0.55 eV and LUMO at −2.09 eV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, is proposed. Curcumin has a HOMO–LUMO gap of 2.64 eV in the visible range . The HOMO of curcumin is at 0.55 eV and LUMO at −2.09 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Here, Ag functions as the plasmonic component and on irradiation by light of appropriate frequency can concentrate the local electric field and boost it. As mentioned earlier, the semiconductor Ag 2 O has a narrow band (1.2-1.4 eV) gap and the HOMO-LUMO gap of curcumin is in the visible range (28). This study first presents the single-step green synthesis of Ag/Ag 2 O nanocomposite particles, with curcumin acting as the reducing as well as stabilizing agent.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, ZnO nanostructures resulted suitable for absorption in ultraviolet rather than visible light because of the wide bandgap (3.3 eV). Hybrid ZnO was synthesized with organic dye-sensitizers, such as 4-((2-hydroxynaphthalen-1-yl)diazenyl)benzoic acid (4ABBN), by precipitation or sol-gel route, for enhanced H 2 generation from water-methanol solution without co-catalysts [84], as well as curcumin by precipitation, for the degradation of polycyclic aromatic hydrocarbons in daylight conditions [82]. ZnO nanorods with adsorbed fluorescein, perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA), or protoporphyrin provided enhanced visible-light degradation of dyes and resorcinol [81].…”
Section: Other Organic Dye-sensitized Semiconductorsmentioning
confidence: 99%
“…Contrary to this, very little research has been reported in the fabrication of hybrids of wide bandgap semiconductors and organic molecules with visible range HOMO‐LUMO gap. Among various possibilities, the potential of curcumin for making such hybrids has been investigated by a few researchers, since the HOMO‐LUMO difference of curcumin is also in the visible light energy range . Thus, curcumin has been applied as an efficient photosensitizer in a dye‐sensitized solar cell .…”
Section: Introductionmentioning
confidence: 99%